Hands-on robotics programming with C++ : leverage raspberry pi 3 and c++ libraries to build intelligent robotics applications /: leverage raspberry pi 3 and c++ libraries to build intelligent robotics applications. (2019) - Tavasalkar, Dinesh
No abstract available